2019
DOI: 10.1159/000501281
|View full text |Cite
|
Sign up to set email alerts
|

Important Clinical Factors in Sequential Therapy Including Lenvatinib against Unresectable Hepatocellular Carcinoma

Abstract: <b><i>Background/Aim:</i></b> We evaluated clinical factors related to improved prognosis of unresectable hepatocellular carcinoma patients (u-HCC), who were treated with tyrosine kinase inhibitor (TKI) sequential therapy, including lenvatinib (LEN). <b><i>Materials/Methods:</i></b> We enrolled 84 u-HCC cases treated with TKIs including LEN from March 2018 to January 2019 (median age 71 years, 63 males, Child-Pugh score (CPS) 5/6/7 = 62/21/1, tumor-node-metastasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
75
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 31 publications
7
75
2
Order By: Relevance
“…Physicians sometimes reduce lenvatinib doses due to lenvatinib-related AEs. 4,[14][15][16][17][22][23][24][25][26] In the present study, the most frequent cause that led to dose reduction or discontinuation of lenvatinib within 6 weeks was appetite loss (72.5%), and the median 2-6 W-RDI (69.6%) was significantly lower than the median 0-2 W-RDI (100%) due to the dose reduction or temporary interruption of lenvatinib. Hiraoka et al reported that appetite loss was an important AE in lenvatinib treatment for discontinuation clinically.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Physicians sometimes reduce lenvatinib doses due to lenvatinib-related AEs. 4,[14][15][16][17][22][23][24][25][26] In the present study, the most frequent cause that led to dose reduction or discontinuation of lenvatinib within 6 weeks was appetite loss (72.5%), and the median 2-6 W-RDI (69.6%) was significantly lower than the median 0-2 W-RDI (100%) due to the dose reduction or temporary interruption of lenvatinib. Hiraoka et al reported that appetite loss was an important AE in lenvatinib treatment for discontinuation clinically.…”
Section: Discussionmentioning
confidence: 44%
“…There have been several reports on the evaluation of antitumor response to lenvatinib using initial imaging, which were assessed from 4 to 8 weeks after lenvatinib introduction, in clinical practice. [14][15][16][17][22][23][24][25][26] These reports showed ORRs of 29.4-45.0% and DCRs of 60.0-93.0%. Similarly, the present study showed that relative to the image at baseline, the 6 W-ORR and 6 W-DCR were 50.0% and 90.0%, respectively.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Thus, if possible, it is important to introduce TKI drug treatment for u-HCC patients with better hepatic functional reserve first, in order to increase the possibility of sequential TKI treatments as postprogression therapy to improve OS. In fact, better hepatic function has been reported to be the only significant factor for sequential TKI therapy in u-HCC patients [32,33]. Those reports also suggested that the most suitable factor for showing hepatic function was an ALBI score of −2.53 [32] or −2.56 [33], which is approximate to the present cut-off for the best ALBI grade of 1 (−2.60).…”
Section: Discussionmentioning
confidence: 83%
“…In fact, better hepatic function has been reported to be the only significant factor for sequential TKI therapy in u-HCC patients [32,33]. Those reports also suggested that the most suitable factor for showing hepatic function was an ALBI score of −2.53 [32] or −2.56 [33], which is approximate to the present cut-off for the best ALBI grade of 1 (−2.60). Additionally, mALBI grade 2a (≤-2.27) has been suggested to be the lowest acceptable grade for introducing not only any TKI as first-line therapy but also LEN at any time to improve OS [28,33].…”
Section: Discussionmentioning
confidence: 83%